Prevalência de Candidatus Mycoplasma haemobos e Ehrlichia sp. em bovinos leiteiros de agricultura familiar de Ji-Paraná, Rondônia - Witter, Rute (2016)
The dairy cattle is directly influenced by the presence of disease in the herd. Thus, we conducted a search of two bacteria hitherto little studied in dairy cattle in Brazil. During the months of September 2012 to November 2013 were collected 320 blood samples and 320 serum samples from 64 properties in the city of Ji-Paraná. Through the Polymerase Chain Reaction (PCR) for the specific 16S rRNA gene for ‘Ca. M. haemobos’ and a PCR heminested for dsb gene of Ehrlichia sp., we determined the prevalence of these two agents. Serologic analysis was performed by indirect immunofluorescence (IFA), and used the strain Cuiabá 16 to Ehrlichia canis as antigen. Presence of antibodies was observed in 178/320 (53.96%) cattle, with endpoint titers ranging from 40 to 5,120. Only 4 properties not had at least one positive bovine. Molecular analysis, 15/320 (4.69%) cattle were positive for E. minasensis, and these samples formed a sequence (295 basis pairs - bp) and was deposited in GenBank accession number KT314243. Here ‘Ca. M. haemobos’, 207/320 (64.2%) cattle have proved positive, with only 3 properties not had at least one positive bovine. Of these, seven positive samples were selected and sequenced, which formed two sequences (460pb) with difference in a one nucleotide. These sequences were deposited in GenBank with KT314241 and KT314242 access numbers. In the questionnaire analysis of the variable 'Number of females over 24 months' was significant for infection ‘Ca. M. haemobos’ (p=0.0372) and in the presence of antibodies to Ehrlichia sp. (p=0.0103). These data provide evidence of natural infection of both agents to cattle in the area. Implications for herd health were discussed